The definitive guide to AdonisJs : building Node.js applications with JavaScript - Pitt, Christopher (Apress, 2018)
Learn everything you need to master the AdonisJs framework, including topics such as interacting with a database, rendering templates, writing asynchronous code, and hosting sites with SSL. Along the way, you'll see how to build a commerce application, which lists products and allows shoppers to register and purchase those products. The site will feature a product catalog, a shopping cart, user registration and login, and profile management. The Definitive Guide to AdonisJs also covers how to create a front-end build chain, so that you can use a modern front-end framework, such as React. You'll discover how to connect your front end to the server, so that data and transactions can be shared between the two. Finally, you'll see how to secure and deploy the application to a virtual private server, including how to apply for and install an SSL certificate and start accepting payments. After reading and using this book, you'll know all you need about AdonisJs. You'll have the tools to turn that side-project you've been thinking about into a real money-making product. It is written by a web expert and reviewed by the AdonisJs project lead. This is the complete start-to-finish guide you've been waiting for. You will: Set up Node.js and AdonisJs, so that you can start building your application Create and use views and template code Implement cooperative multitasking, in JavaScript Represent eventual values with AdonisJs promises Organize and isolate your code in controllers and decorate them with middleware, to do things like authentication Build queries, using the Lucid DSL, and package these database entities up into model classes Validate form data and respond with the appropriate error messages Respond to general framework errors with custom error pages Learn the deeper parts of sessions and cookies Update the state of the user interface with WebSockets Host AdonisJs applications in a modern hosting environment.